Photoelectron spectroscopy of undercoordinated atoms on various morphologic surfaces - Nie, Yanguang (2012)
Behavior of the local bonds and the energetic electrons associated with ill-coordinated atoms and their response to the environment and applied stimuli dictate the unusual performance of materials at defect, edge, surface, vacancy, grain boundary, impurity, interface, and at the nanoscale in catalytic reaction, growth nucleation, friction, corrosion and radiation protection, etc. Although the chemistry and physics of materials at these specific sites have been intensively investigated for more half a century, the laws governing the performance of the ill-coordinated atoms remain as yet unestablished. With the aid of the bond order-length-strength (BOLS) correlation and the tight binding (TB) approximation, this thesis focuses on the development and application of the atomistic photoelectron distillation spectroscopy (APDS), which has enabled us to solve the most significant and outstanding challenge by zooming in the bonds and electrons within the atomic patches surrounding the under- and hetero-coordinated atoms. We have conducted in situ X-ray photoelectron spectroscopy (XPS) measurements on Ni, Cu and Pt metal nanoparticles deposited on different substrates and the atomic vacancy defects on graphite surface. We have also analyzed the available spectral data systematically from the perspective of bond and nonbond formation, dissociation relaxation and vibration and the associated energetic and dynamics of electrons in the repopulation, localization, densification and polarization.